The future of adhesion prophylaxis trials in abdominal surgery: an expert global consensus - Wilde, Rudy Leon de; Devassy, Rajesh; Broek, Richard P. G. ten; Miller, Charles E.; Adlan, Aizura; Aquino, Prudence; Becker, Sven; Darmawan, Ferry; Gergolet, Marco; Habana, Maria Antonia E.; Khoo, Chong Kiat; Koninckx, Philippe R.; et al. (Journal of Clinical Medicine, 2022)
Postoperative adhesions represent a frequent complication of abdominal surgery. Adhesions can result from infection, ischemia, and foreign body reaction, but commonly develop after any surgical procedure. The morbidity caused by adhesions affects quality of life and, therefore, it is paramount to continue to raise awareness and scientific recognition of the burden of adhesions in healthcare and clinical research. This 2021 Global Expert Consensus Group worked together to produce consented statements to guide future clinical research trials and advise regulatory authorities. It is critical to harmonize the expectations of research, to both develop and bring to market improved anti-adhesion therapies, with the ultimate, shared goal of improved patient outcomes.